1998
DOI: 10.1007/s004649900612
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic insufflation of the abdomen reduces portal venous flow

Abstract: The increased intraperitoneal pressure necessary to perform laparoscopic operations reduces substantially the portal venous flow. The extent of the volume flow reduction is related to the level of intraperitoneal pressure. This reduction of flow may depress the hepatic reticular endothelial function (possibly enhancing tumor cell spread). In contrast, the reduced portal flow may enhance cryoablative effect during laparoscopic cryosurgery for metastatic liver disease by diminishing the heat sink effect. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
223
1
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(244 citation statements)
references
References 13 publications
9
223
1
8
Order By: Relevance
“…These factors were proved to make a significant change in intra-abdominal blood flow, which could have eventually been a cause of PVT. 2 Therefore, this restricted information may be a limitation of our case report.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These factors were proved to make a significant change in intra-abdominal blood flow, which could have eventually been a cause of PVT. 2 Therefore, this restricted information may be a limitation of our case report.…”
Section: Discussionmentioning
confidence: 96%
“…1 However, laparoscopic surgery has been suggested to cause portomesenteric vein thrombosis (PVT) attributed to decreased portomesenteric blood flow due to increased abdominal pressure and hypercapnia. 2 PVT after laparoscopic appendectomy is an uncommon complication.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that pneumoperitoneum during laparoscopic procedures can decrease intra-abdominal blood perfusion [13][14][15] and thereby act as a cause of PMVT. 16 In surgical planning for our case, we considered using gasless abdominal wall lifting instead of pneumoperitoneum, to avoid decreasing intra-abdominal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…There are various haemodynamic, respiratory, and stress response changes in laparoscopic surgery due to creation of pneumoperitoneum. [7][8][9][10] In balanced anaesthesia, ideal opioid would permit rapid titration to the effect, successfully prevent unwanted responses to various stimuli, require little supplementation, does not depress cardiovascular function, permit the return of adequate spontaneous ventilation in timely manner and produce residual if not complete post-operative analgesia with minimal side effects. Both the group of drugs have haemodynamic stability, analgesia, sedation and decreases the requirement of other anesthetic drugs and is available at low cost.…”
Section: Discussionmentioning
confidence: 99%